Plan estrategico para el desarrollo institucional de la unidad educativa “24 de mayo” Cantón Quevedo, período 2015 – 2019 - Betancourt Peralta, Hodalys Virvanys (2016)
Currently, several institutions have seen the need to incorporate activities planning systems that enable it to achieve its objectives and goals redirect functions and processes to improve competitively. This research work aims to develop a strategic plan for Educational unit "May 24", with the aim of improving institutional development through the development and implementation of a strategic plan. To carry out this research work will have reliable information which will be provided by the highest authority of the institution, it should be emphasized that the research to be done is of great importance to the educational unit May 24 as it will be possible to regulate and measure the activities that develop within the institution to achieve the strategic objectives. To carry out the strategic plan began defending the mission, vision and institutional principles that will be clear the way for the institution and lay a solid foundation for institutional development. Within the development of a strategic plan objectives and specific parameters which will measure the efficiency and effectiveness of the institution's strategic plan specifically provides for the development of the SWOT matrix and its interpretation which identify the current situation sets in the institutional development of the Education Unit "May 24".